2020
DOI: 10.1051/0004-6361/202038020
|View full text |Cite
|
Sign up to set email alerts
|

A naked-eye triple system with a nonaccreting black hole in the inner binary

Abstract: Several dozen optical echelle spectra demonstrate that HR 6819 is a hierarchical triple. A classical Be star is in a wide orbit with an unconstrained period around an inner 40 d binary consisting of a B3 III star and an unseen companion in a circular orbit. The radial-velocity semi-amplitude of 61.3 km s−1 of the inner star and its minimum (probable) mass of 5.0 M⊙ (6.3 ± 0.7 M⊙) imply a mass of the unseen object of ≥4.2 M⊙ (≥5.0 ± 0.4 M⊙), that is, a black hole (BH). The spectroscopic time series is stunningl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
146
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 66 publications
(95 reference statements)
9
146
2
Order By: Relevance
“…The second system that was recently proposed to contain a stellar-mass BH is HR 6819 (Rivinius et al 2020). It was reported to be variable already by Buscombe & Morris (1960).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The second system that was recently proposed to contain a stellar-mass BH is HR 6819 (Rivinius et al 2020). It was reported to be variable already by Buscombe & Morris (1960).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rivinius et al (2020) suggested that HR 6819 hosts the closest stellar-mass BH to the Sun yet reported. They argued that the emission profiles attributed to the rapidly-rotating Be star are stationary on the time scale of years, and that the Be star seen in the spectrum must therefore be a distant tertiary in an outer orbit.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations